Toward a Systemic Understanding of Listeria monocytogenes Metabolism during Infection - Fuchs, Thilo M.; Eisenreich, Wolfgang; Kern, Tanja; Dandekar, Thomas (Frontiers in Microbiology, 2012)
Listeria monocytogenes is a foodborne human pathogen that can cause invasive infection in susceptible animals and humans. For proliferation within hosts, this facultative intracellular pathogen uses a reservoir of specific metabolic pathways, transporter and enzymatic functions whose expression requires the coordinated activity of a complex regulatory network. The highly adapted metabolism of L. monocytogenes strongly depends on the nutrient composition of various milieus encountered during infection. Transcriptomic and proteomic studies revealed the spatial-temporal dynamic of gene expression of this pathogen during replication within cultured cells or in vivo. Metabolic clues are the utilization of unusual C2- and C3-bodies, the metabolism of pyruvate, thiamine availability, the uptake of peptides, the acquisition or biosynthesis of certain amino acids, and the degradation of glucose-phosphate via the pentose phosphate pathway. These examples illustrate the interference of in vivo conditions with energy, carbon and nitrogen metabolism, thus affecting listerial growth. The exploitation, analysis and modelling of the available data sets served as a first attempt to a systemic understanding of listerial metabolism during infection. L. monocytogenes might serve as a model organism for systems biology of a Gram-positive, facultative intracellular bacterium.